Changing concepts and educational paradigm in the frame of ODL - Anderson, Pia Guttorm; Hansen, Ole (Proceedings of the International Conference on Networked Learning, 2000)
Under the motto: "Knowledge without frontiers" TESS Network® has developed new ways for the educational thinking. The project, SocraTESS ODL Network, which is founded by the Socrates programme, ODL action is an example on how the use of open and distance learning (ODL) has played a part in creating change and development in both the traditional in-service training of teachers as well as in the teaching methods and their attitude towards educational change.